Mucosal Proliferations in Completely Examined Fallopian Tubes Accompanying Ovarian Low-grade Serous Tumors: Neoplastic Precursor Lesions or Normal Variants of Benign Mucosa?. (May 2018) - Wolsky, Rebecca J.; Price, Matt A.; Zaloudek, Charles J.; Rabban, Joseph T.
Abstract : Malignant transformation of the fallopian tube mucosa, followed by exfoliation of malignant cells onto ovarian and/or peritoneal surfaces, has been implicated as the origin of most pelvic high-grade serous carcinoma. Whether a parallel pathway exists for pelvic low-grade serous tumors [ovarian serous borderline tumor (SBT) and low-grade serous carcinoma (LGSC)] remains to be fully elucidated. The literature is challenging to interpret due to variation in the diagnostic criteria and terminology for cytologically low-grade proliferations of the fallopian tube mucosa, as well as variation in fallopian tube specimen sampling. Recently, a candidate fallopian tube precursor to ovarian SBT, so-called papillary tubal hyperplasia, was described in advanced stage patients. The current study was designed to identify fallopian tube mucosal proliferations unique to patients with low-grade serous ovarian tumors (serous cystadenoma, SBT, LGSC) and to determine if they may represent precursors to the ovarian tumors. Fallopian tubes were thinly sliced and entirely examined microscopically, including all of the fimbriated and nonfimbriated portions of the tubes, from patients with ovarian serous cystadenoma (35), SBT (61), and LGSC (11) and from a control population of patients with ovarian mucinous cystadenoma (28), mature cystic teratoma (18) or uterine leiomyoma (14). The slides of the fallopian tubes were examined in randomized order, without knowledge of the clinical history or findings in the ovaries or other organs. Alterations of the mucosa of the fallopian tube were classified as type 1: nonpapillary proliferation of cytologically bland tubal epithelium exhibiting crowding, stratification, and/or tufting without papillary fibrovascular cores or as type 2: papillary alterations consisting of a fibrovascular core lined by a cytologically bland layer of tubal epithelium. A third abnormality, type 3, consisted of detached intraluminal papillae, buds, or nests of epithelium that cytologically resembled the epithelial component of SBT or LGSC. Mucosal proliferations were identified in subsets of all populations, including the control populations. Overall, type 1 proliferations were in 28% to 61% of all patients and type 2 alterations in 4% to 16%. There was no statistically significant difference in the incidence of type 1 or type 2 proliferations between the class of ovarian serous tumors (benign, SBT, LGSC), between early and advanced stage SBT, or between patients with any ovarian serous tumor and the control population of nonserous diagnoses. Type 3 alterations were only identified in patients with advanced stage SBT/LGSC and not in any early stage SBT or cystadenoma. These findings suggest that type 3 alterations floating in the fallopian tube lumen represent exfoliation of tumor cells from ovarian and/or peritoneal origin. Our study did not identify a mucosal-based proliferation of the fallopian tubes that was specific to ovarian low-grade serous tumors. Cytologically bland mucosal proliferations appear to be common in fallopian tubes from patients of all ages and unrelated to ovarian tumorigenesis. A consensus on diagnostic criteria and terminology for these types of proliferations is needed, as well as further study into their etiology, including possible association with hormonal environment.